Novel Interecting Blends Based on Amino Terminited Oligoimides by Using Michael Addition Reaction-II - Rita R. Patel; Mukesh C. Patel (E-Journal of Chemistry)
New amino terminated oligoimides (AOIs) were prepared by the Michael addition reaction of various bismaleimide (1), namely, 1-(4-((4-((2, 5-dioxocyclopent-3 enylamino) methyl) cyclohexyl) methyl) cyclohexyl)-1, 6-dihydropyridine-2, 5-dione with excess of various diamines (2a-c). These AOIs were characterized by elemental analysis, FT-IR spectral studies and number average molecular weight estimated by non-aqueous conductometric titrations. AOIs were then treated with acrylol chloride and resultant acryl terminated oligoimides (AcOIs) samples were also characterized thermogravimetrically. Each of these AcOI was then combined with the N-phenyl maleimide (PM) in THF solvent. The resultant suspensions were then heated in the presence of azobisisobutyronitrile (AIBN) as an initiator. The AcOI and PM polymerized through double bond simultaneously and form interacting blends, which were analyzed thermogravimetrically. The glass fiber reinforced composites were fabricated by using the suspensions of the AcOI and PM. The composites of Interacting blends were analyzed for their mechanical, chemical and electrical properties.